2020
DOI: 10.3889/oamjms.2020.4850
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Light-curing Intensity Output and Students’ Knowledge among Dental Schools in Riyadh City

Abstract: AIM: The aim of this study is interpreting the dental student’s knowledge of light-curing units from different universities and colleges in Riyadh city and to evaluate the intensity of the light output of light-emitting diode (LED)-curing devices in dental school clinics in Riyadh, Saudi Arabia. METHODS: One hundred eighty-two visible light-curing (VLC) units were randomly selected to have their light intensity output evaluated using Demetron® L.E.D. Radiometer – Kerr among dental school clinics in Riyad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Even though these restorative materials have gained popularity over the past few years, the failure rate is higher than anticipated. Several factors affect the polymerization of a composite resin restoration: technical factors such as the irradiance and type of Light-Curing Unit (LCU), material-related factors such as the resin shade and thickness, and operator factors such as the light tip position and exposure time [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though these restorative materials have gained popularity over the past few years, the failure rate is higher than anticipated. Several factors affect the polymerization of a composite resin restoration: technical factors such as the irradiance and type of Light-Curing Unit (LCU), material-related factors such as the resin shade and thickness, and operator factors such as the light tip position and exposure time [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…8,15,16 Several cross-sectional studies have revealed significant knowledge and practice gaps among dental clinicians, interns, and students. [17][18][19][20][21][22][23] These findings have highlighted critical areas for improvement, emphasizing the importance of patient safety. Dental assistants (DAs) are integral members of dental practice.…”
Section: Introductionmentioning
confidence: 99%